Pathogenicity and Effectiveness of Entomopathogen Nematode Heterorhabditis sp. to Potato Tuber Moth Phthorimaea operculella (Zeller)(Lepidoptera: Gelechiidae) PATOGENISITAS DAN KEEFEKTIFAN NEMATODA ENTOMOPATOGEN Heterorhabditis sp. TERHADAP PENGGEREK UMBI - Lufthi Rusniarsyah; Aunu Rauf; Supramana .; Samsudin . (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2015)
Potato tuber moth, Phthorimaea operculella Zell. (Lepidoptera: Gelechiidae) is one of the important potato pest. Damage occurs in the field as well as in the storage warehouses. If control is not performed well, the potential loss will reach almost 100%. The effectiveness of entomopathogenic nematodes of the Heterorhabditis has been studied to control several crop pests. Infective juveniles (IJ’s) of nematodes are capable to seek and infect insects that live in soil and in plant tissues. The objectives of the research are to study the pathogenicity of the Heterorhabditis sp. against P. operculella in the laboratory in direct treatment and in the potato tuber. The experiment was employed a completely randomized design with 6 treatments and 4 replications. The treatment tested are the density level of nematodes Heterorhabditis sp. (100, 200, 300, 400, and 500 IJ/ml) and the control. The results showed that P. operculella infected by Heterorhabditis sp. has symptoms of decreasing motion and feeding activity. Dead insects have change color to dark brown and the body become soft. Heterorhabditis sp. can kill P. operculella within 12 hours after application (HAA). At density level 100 IJ/ml it can control P. operculella by 85% within 24 HAA. The mortality rates of P. operculella in the tubers was 35% at doses of 1000 IJ/tubers, although the ANOVA test was not significantly different.Key words: Phthorimaea operculella, entomopathogenic nematodes, Heterorhabditis sp.